Conscientious objection as a form of exercising freedom of conscience and religion – the context of refusal to perform an abortion or to participate in procedures related to its performance by medical personnel in the Polish legal order - Zalewski, Bartosz (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
This chapter aims to analyse the concept of the right to conscientious objection (conscience clause) in the constitutional context. In its judgment of 7 October 2015, Poland’s Constitutional Tribunal finally confirmed that the right to conscientious objection is an integral part of the constitutionally guaranteed freedom of conscience. For this reason, the right to conscientious objection is legally guaranteed by the Polish Constitution. This leads both to proposing an appropriate concept of conscience consistent with Polish constitutional axiology and to formulating de lege ferenda conclusions.